2018
DOI: 10.1590/1807-3107bor-2018.vol32.0093
|View full text |Cite
|
Sign up to set email alerts
|

Expression of urokinase-type plasminogen activator and its receptor in squamous cell carcinoma of the oral tongue

Abstract: Urokinase-type plasminogen activator (uPA) and its receptor (uPAR) act in the proteolysis of basement membrane and extracellular matrix structures, facilitating tumor invasion. The purpose of this study was to evaluate the relationship between these proteins and clinicopathological parameters in squamous cell carcinoma of the oral tongue (SCCOT). Sixty cases of SCCOT were submitted to immunohistochemistry and analyzed semiquantitatively at the invasion front and in the tumor core. The results were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Interpretation is further limited by the small sample size, especially for subgroup analyses. However, even with large cohorts and validated antibodies, staining results can vary depending on the representative tumor specimen and scoring method chosen [45].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation is further limited by the small sample size, especially for subgroup analyses. However, even with large cohorts and validated antibodies, staining results can vary depending on the representative tumor specimen and scoring method chosen [45].…”
Section: Discussionmentioning
confidence: 99%
“…They found a global elevation of both proteases, without a true superiority of either the activator or inhibitor of plasminogen [104]. Serpa et al also found elevated uPA levels in a similar study conducted on human tongue SCC and showed that SCC cells had an elevation in the expression of uPAR [105]. Baker et al conducted a more complete study and showed an elevation in uPA, uPAR, PAI-1 and PAI-2 expression in human OSCC tumor tissue.…”
Section: Biological/fundamental Research Contributionsmentioning
confidence: 99%
“…In the colorectal, stomach, and oral cavity, increased expression of uPA was observed. Marianna et al reported that uPA is highly expressed in high-grade tumors and in the worst invasive mode, and is involved in the progression of OSTCC to poor prognosis (23). Serpin family E member 1 (SERPINE1), a serine proteinase inhibitor (serpin), is the main inhibitor of tissue plasminogen activator (tPA) and urokinase (uPA).…”
Section: Discussionmentioning
confidence: 99%